If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5z + -3 = 17 Reorder the terms: -3 + 5z = 17 Solving -3 + 5z = 17 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 5z = 17 + 3 Combine like terms: -3 + 3 = 0 0 + 5z = 17 + 3 5z = 17 + 3 Combine like terms: 17 + 3 = 20 5z = 20 Divide each side by '5'. z = 4 Simplifying z = 4
| 7a^2-64a+64=0 | | x^2=7.84+2*0.0209625668*133 | | 0=ln(x-5) | | 3(p-4)=36 | | 5m^2-42m+49=0 | | 9x+12-8x=-6+(-4) | | 96-7x=29x+20 | | 320=187+133.578499968x+0.5*-0.0209625668*17843.21565 | | k-273.15=c | | -x+8x=-38-4 | | 9-10x=145-38x | | X^5+3x^4-189x^3+797x^2-612x=0 | | -7x+3x=-50-2 | | 26+x=-26 | | 16=2+7x | | 5x+21=12x-14 | | 155-5x=4x+20 | | 125m-75m+48500=50500-200m | | 0.385*t=-9 | | -5x^2+26x+24=0 | | 10a^2+7a^2+1a= | | x+20+44x+3x=180 | | 125m-75m+48500=50500-200 | | 3(x+5)=x+15 | | 294s-160-5s=-5 | | 28-9x=11+8x | | 5x-(x-3)-1=18 | | 34-5x=20+9x | | x^3-4x^2+9=0 | | 3(2y-1)=-8(6+y) | | 82-(6x+6)=6(x+4)+x | | x^2+9x-32=0 |